2022
DOI: 10.1017/s0007114522001295
|View full text |Cite
|
Sign up to set email alerts
|

Dietary trajectories through the life course: opportunities and challenges

Abstract: Studying the dynamic patterns of dietary changes or stability (otherwise known as dietary trajectories) across the life course can provide important information about when and in whom to intervene with nutritional interventions. This article reviews evidence from longitudinal studies that describe dietary trajectories through the different life stages, covering early life, adolescence to young adulthood and from mid to late adulthood. Current findings suggest that the establishment of diet patterns likely occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Therefore, a dietary pattern does not remain stagnant. We can speculate about the emergence of a new stage of the nutrition transition process, as a consequence of the desire to prevent or delay degenerative diseases and extend good health, with the adoption of a better quality diet and higher amount of fruit, vegetables and whole grains ( 39 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a dietary pattern does not remain stagnant. We can speculate about the emergence of a new stage of the nutrition transition process, as a consequence of the desire to prevent or delay degenerative diseases and extend good health, with the adoption of a better quality diet and higher amount of fruit, vegetables and whole grains ( 39 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic analysis of diet-related health risks in 195 countries found that suboptimal diet, particularly high sodium intake and low fruit and whole grain intakes, contributed to substantial burdens of NCD mortality and morbidity among adults aged 25 years and above (Afshin et al, 2019). However, once individuals enter adult life, dietary patterns are fairly stable and tend to track over time (Craigie et al 2011;Chong, 2022). The developmental stage of early adulthood may therefore represent a transition from adolescence to adulthood and a window for the development of a high-quality diet to prevent NCD in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout life, the quality of an individual’s dietary patterns can affect health in later years as well as life expectancy [ 5 , 6 , 7 , 8 , 9 ]. There is also evidence that dietary patterns during selected life stages can influence eating practices later in life [ 10 , 11 , 12 , 13 ]. For instance, food preferences early in life set the foundation for food choices and eating habits in later childhood and adulthood [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The group-based trajectory modeling (GBTM) method has been used to explore dietary pattern trajectories since 2014 [ 13 , 14 , 18 , 20 ]. This method uses longitudinal data to account for between-individual variation and describe the continuity of different behaviors of groups of individuals through time [ 21 ].…”
Section: Introductionmentioning
confidence: 99%